Analysis of Sleep Quality and TCM Constitution Characteristics in 258 Outpatients: A Cross-Sectional Study Based on Outpatient Cases - Chang Liu; Jing Qu; Luquan Chen; Ruijie Liu (Applied Bionics and Biomechanics)
Objective. To explore the correlation between traditional Chinese medicine (TCM) constitutions and insomnia by studying the distribution characteristics of different TCM constitutions in an outpatient insomnia population. Methods. From November 2020 to March 2021, 258 patients in the outpatient department of the Traditional Medicine Department of Tongren Hospital were interviewed using some questionnaires (Athens Insomnia Scale and constitution of traditional Chinese medicine), and correlation analysis was conducted. Results. The participants consisted of 152 (58.91%) insomniacs and 106 (41.09%) noninsomniacs. The top four biased constitutions of the insomniac population (the same patient may have two or more constitutions simultaneously), as determined from the proportions of constitutions in ascending order, are as follows: Qi deficiency constitution, 95 cases (62.50%); Yang deficiency constitution, 85 cases (45.95%); blood stasis, 70 cases (37.84%); and qi stagnation, 65 cases (35.14%). The results of the Spearman correlation analysis showed that the standard scores of qi deficiency, Yang deficiency, blood stasis, and Qi stagnation were positively correlated with the total score of AIS (P<0.05). Conclusion. Insomnia is correlated and the TCM constitution bias, Qi deficiency, Yang deficiency, blood stasis, and Qi stagnation exhibiting the highest correlation.